Peran Kecanduan Game Online terhadap Regulasi Emosi pada Generasi Z - William Victorio; Agustina Agustina (Lembaga Yasin AlSys, 2025)
Online game addiction is an increasingly prominent phenomenon among Generation Z, a cohort closely connected to digital technologies and at heightened risk of experiencing difficulties in emotion regulation. This study aims to analyze the role of online game addiction in emotion regulation among Generation Z. A quantitative approach with purposive sampling was employed, involving 194 participants aged 17–28 years who played online games for 20–30 hours per week. The research instruments consisted of the Indonesian Game Addiction Questionnaire (IGAQ) to measure the level of online game addiction and the Emotion Regulation Questionnaire (ERQ) to assess emotion regulation. Simple linear regression analysis showed that online game addiction has a significant effect on emotion regulation (R² = 0.687; p < 0.001), indicating that 68.7% of the variance in emotion regulation is explained by online game addiction. The negative relationship suggests that the higher the level of online game addiction, the lower the individual’s ability to manage and express emotions adaptively. Additional analyses also revealed significant negative associations for both cognitive reappraisal and expressive suppression. These findings confirm that online game addiction is an important factor influencing the emotional balance of Generation Z and should be a key target in mental health promotion and prevention efforts.